CT Evaluation of Liver Hydatid Disease - Ameen, May Khalid (Journal of the Faculty of Medicine Baghdad, 2007)
Background: To elucidate distinctive CT imaging features that allows a diagnosis of hepatic hydatidosis. Patients and methods : The computed tomographic (CT) findings of 58 patients with sonographically detected cystic liver lesions were prospectively analyzed. These patients were followed up until a final diagnosis was reached. Results : By CT scanning we correctly localized and diagnosed 81 hepatic hydatid cysts in 50 patients. These were all proved by surgery or endoscopic retrograde cholangio-pancreatography (ERCP). Stage III and II hydatid cysts were the commonest types (29 % and 25 % respectively ). 52 % of the cysts were 5-10 cm at presentation. At CT, we identified some ancillary imaging features that help in the diagnosis of unilocular type I hepatic echinococcal cysts. Conclusion : Although no imaging feature can provide a definitive diagnosis of a unilocular type I hepatic echinococcal cyst, some ancillary imaging features may help in differentiating them from a non parasitic simple liver cysts. Types II, III, & V hydatid cysts, on the other hand, have characteristic imaging features that allow their confidant diagnosis.